Çağdaş heykelde heykel kaide ilişkisi - Salor, Füsun (My University, 1998)
Bu çalışmanın amacı heykel ile kaidenin ilişkisini irdelemek ve günümüz heykel sanatının geldiği noktada heykelin ve taşıyıcısı olan kaidenin geçirdiği evreleri araştırmaktır. Sanat tarihçi E.H. Gombnch'm dediği gibi Sanatın tüm tarihi gittikçe gelişen teknik yetkinleşmenin tarihi değil, değişen kafa yapılanmn ve gereksinmelerin tarihidir. Bu bağlamda ilk çağdan bu yana sanatın kendi, programım belirlediğini söyleyebiliriz. Heykel sanatının gelişimi başlangıcından bu yana pek çok konu üzerinde tüm kültürlerde rol oynamış, her dönemde kendi toplumuna hizmet vermiş var olan düşünce sistemleri içinde varlığını sürdürmüştür. Bu incelemede 20. y.y. gelinceye kadar geçirilen dönemlerde heykelin tema, malzeme ve biçim olarak büyük farlılıklara uğramadığı görülmektedir. Değişen ve gelişen düşüncelerin koşutluğunda heykel sanatı, telmolojinin de biçime yansımasıyla günümüze kadar gelmiştir. Günümüz heykel sanatına bakıldığında heykelin kaidesiyle olan ilişkisinden çok, yapılan işlerin düşünsel boyutunun biçimi oluşturduğu görülmektedir.

The aim of this study is to analise the relation between a statue and its base and to search for the evolutions undergone by the statue and its carrying base at a point reached by today's art of sculpture. As E.H.Gombrich, a historiographer of art, says, The whole history of art is not a history of an increasingly developing technical qualification, but it is the history of gradually changing structure of mentality. In this context, we can say that the art itself has determined its own programme since the first historical period till today. The development of the art of sculpture has played a major role on many subjects in all cultures from its starting till today, and always maintained its presence in the existing systems of thought that have served for its own community during each period. In this study, it is seen that the period passed until having reached the 20th Century has not revealed any major differences from the standpoints of theme, material and shape. In parallel with gradually changing and developing thoughts, the art of sculpture has come up to our time with the reflection of technology onto shape as well. Looking at today's art of sculpture, it is seen that the works performed rather than the relation between a statue and its base constitute the form of its mental dimension.
Keywords: Heykel